2021
DOI: 10.1093/molbev/msaa335
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Pleiotropic Hub Gene Expression Is Associated with Interspecific Differences in Head Shape and Eye Size in Drosophila

Abstract: Revealing the mechanisms underlying the breathtaking morphological diversity observed in nature is a major challenge in Biology. It has been established that recurrent mutations in hotspot genes cause the repeated evolution of morphological traits, such as body pigmentation or the gain and loss of structures. To date, however, it remains elusive whether hotspot genes contribute to natural variation in the size and shape of organs. As natural variation in head morphology is pervasive in Drosophila, we studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 140 publications
0
28
0
Order By: Relevance
“…Concordant findings from contemporary studies with respect to the meta-signature are summarized in S6 Table . Systems biology insights on miRNA-T2D associations, rendered by network analyses are noteworthy. Since the two hub nodes (hsa-miR-106b-5p & hsa-miR-15b-5p) which formed epicenters of the two most densely and extensively connected sub-networks might have crucial functional roles as well [35,36], further research on their roles on T2D pathogenesis is warranted. Another insightful observation was the disproportionately high representation of three markers (hsa-miR-15b-5p, hsa-miR-106b-3p, hsa-miR-146a-5p) within the miRNA-disease associations network, which suggested that they likely have key roles in the development of not only T2D but also other cardiometabolic diseases and co-morbidities via multiple cross-talk and pleiotropic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordant findings from contemporary studies with respect to the meta-signature are summarized in S6 Table . Systems biology insights on miRNA-T2D associations, rendered by network analyses are noteworthy. Since the two hub nodes (hsa-miR-106b-5p & hsa-miR-15b-5p) which formed epicenters of the two most densely and extensively connected sub-networks might have crucial functional roles as well [35,36], further research on their roles on T2D pathogenesis is warranted. Another insightful observation was the disproportionately high representation of three markers (hsa-miR-15b-5p, hsa-miR-106b-3p, hsa-miR-146a-5p) within the miRNA-disease associations network, which suggested that they likely have key roles in the development of not only T2D but also other cardiometabolic diseases and co-morbidities via multiple cross-talk and pleiotropic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis of the meta-signature was carried out on the miRNet 2.0 [34], which, by default, defines hub-nodes as those miRNAs with above-average degree and betweenness in the miRNA-target gene interactions network. These two measures of centrality can be defined as follows: As the densely and tightly connected hub nodes in biological networks [35] tend to be critical functional regulators as well, they are sought after in precision medicine approaches [36]. We visualized the miRNA-target gene interactions network on miRNet 2.0 and determined the network attributes including hub nodes, modules, and continents versus islands.…”
Section: Network Analysismentioning
confidence: 99%
“…Further studies exploring these interactions could enhance our understanding of the genetic basis of T1D. Hub genes which appear as extensively and densely connected nodes in scale-free gene regulatory networks [50] tend to have important regulatory functions and offer value as potential therapeutic targets [51]. Therefore, hub genes identified in this analysis may be useful for guiding pharmacogenomics studies focused on T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Also, variation in odor guidance to 2,3-butanedione showed genes associated with neural development and the later processing in the central nervous system which might be related to that behavioral variation (Brown et al, 2013 ). This genotypic variation is seen not only at the behavioral level but also, for example, in lifespan or morphological and anatomical traits as brain, wing, thorax, or eye size (Carreira et al, 2016 ; Buchberger et al, 2021 ).…”
Section: Genetic Basis Of Animal Individualitymentioning
confidence: 99%